Peran Ibu dalam Membangun Kesadaran Gender pada Anak-Anak di Komunitas Rural - Kudri, Kudri (Center for Gender and Children Studies, Lembaga Penelitian dan Pengabdian Masyarakat (LP2M) UIN Sultan Thaha Saifuddin Jambi, 2024)
This study examines the role of mothers in educating children about gender awareness in rural communities of Bungo Regency, Jambi Province, with a focus on the influence of traditional social and cultural norms. Through a qualitative approach, data was collected through in-depth interviews, observations, and documentation with housewives as respondents. The results of the study show that traditional values are still very strong and play a big role in determining gender roles, but there are mothers who try to teach gender equality values despite facing various challenges. These findings indicate that gender education by more egalitarian mothers can help children develop a broader view of gender roles and demonstrate a more inclusive attitude. This research provides important insights into social dynamics in rural communities and suggests the need for broader support to drive change towards gender equality.